The lncRNA Jpx participates in testosterone-induced H9c2 cell hypertrophy by targeting the miR-145-5p/Nfatc3 axis - Wen, Mingxing; Zhang, Xinyu; Tong, Litao; Chen, Yuhui; Li, Zhengjie; Wang, Yichen; Liu, Can; Zhang, Jinwei; Ge, Liangpeng; Sun, Jing; Li, Mingzhou; Li, Xuewei; et al. (Frontiers in Cell and Developmental Biology, 2025)
Cardiac hypertrophy is an adaptive cardiac response to overload. The ensuing decompensation eventually leads to heart failure or sudden death. Testosterone can induce cardiomyocyte hypertrophy, although the underlying mechanism has not been completely elucidated. lncRNAs play a vital role in the regulation of cardiac hypertrophy. Jpx is a newly identified lncRNA highly associated with cardiac hypertrophy, although its specific role in cardiac hypertrophy progres-sion remains unclear. Here, we explore the role and underlying mechanism of Jpx in testos-terone-induced cardiomyocyte hypertrophy. Our results show that Jpx is distinctly upregulated in testosterone-induced hypertrophic H9c2 cells. Overexpression of Jpx strikingly enhances testosterone-induced H9c2 cell hypertrophy. Finally, we demonstrate that Jpx acts as an en-dogenous sponge of miR-145-5p, herein identified as a hypertrophy suppressor, and that forced expression of Jpx downregulates miR-145-5p expression to boost Nfatc3 expression and promote hypertrophy. Additionally, a luciferase assay shows that miR-145-5p is a direct target of Jpx, and overexpression of miR-145-5p counteracts the effects of Jpx overexpression on hypertrophic H9c2 cells. Our findings demonstrate that testosterone can induce Jpx expression and that upregulation of Jpx is involved in testosterone-induced H9c2 cell hypertrophy through the miR-145-5p/Nfatc3 axis. Modulation of these may provide a new approach for tackling cardiac hypertrophy.